Cross-lagged panel insights into health, social, and economic in life satisfaction - Siripanich, Pachitjanut; Philmolsri, Titirut; Kaewchankha, Wasin (International Journal of Public Health Science (IJPHS), 2025)
This study examines life satisfaction in older Thai adults as shaped by dynamic interactions among health, social, and economic factors. Most prior research-both globally and in Thailand-has relied on cross-sectional designs, limiting understanding of cross-lagged relationships. Closing this gap led to the following research objectives: i) assess the stability of health, social, and economic factors and life satisfaction, ii) examine reciprocal and temporal relationships among these domains, and iii) explore age-related variations. Data were drawn from Wave III and IV of the Health, Aging, and Retirement in Thailand (HART) survey (n = 561) and analyzed using cross-lagged structural equation modeling. The findings demonstrated stability in social activity, physical health, mental health, and life satisfaction in both waves. Cross-lagged effects revealed reciprocal and temporal relationships, where mental health influenced future physical health, and life satisfaction impacted subsequent mental well-being. Age-specific differences emerged, with stronger effects in middle-aged adults, where life satisfaction had a greater effect on future mental health, and mental health more strongly influenced physical health over time. Among those aged 60 and older, physical health exhibited the highest stability, while life satisfaction and mental health effects weakened, suggesting age-related shifts in well-being.